The Role of Public Relations of the Coordinating Ministry for Economic Affairs in Overcoming Hoaxes on Social Media - Thelma Amelita; Siko Dian Sigit Wiyanto; Irwansyah Irwansyah (Riviera Publishing, 2023)
This research discusses the role of government public relations in tackling hoax news, which is rampant in this era of digitalization. The massive and rapid spread of hoax news on the internet and social media has encouraged government public relations to take steps to overcome this, from managing the issue to the necessary follow-up responses. The approach used in this research is qualitative, with a constructivist paradigm to look for lessons learned using a case study strategy. Data collection techniques were carried out through interviews. Apart from that, observations and documentation were also carried out. This research studies how the concept of public relations strategy is implemented in resolving the cases mentioned in this research. The analysis results found that the role of social media is vital in dealing with hoax news that appears on the internet and social media.